Perancangan Sistem Digitalisasi Penyimpanan Arsip Surat Sekolah Menengah Berbasis Cloud pada Kantor Koordinat Wilayah Kecamatan Meral - Fazaramta Fazaramta; Tri Mardalena; Ilham Gantar Friansyah; Dina Fara Waidah (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
In today's digital era, the need for efficient, secure, and easily accessible document management systems has become increasingly important, especially within government institutions. The District Coordinator Office of Meral Subdistrict, under the Department of Education of Karimun Regency, still relies on conventional paper-based archiving systems. This creates several issues, such as difficulties in document retrieval, the risk of loss or damage to records, and a high dependence on administrative staff. This study aims to design and implement a cloud-based digital archiving system to enhance the efficiency, effectiveness, and security of archive management. The system was developed using the waterfall model, which includes stages of requirements analysis, system design, implementation, and testing. Modeling tools used in the system design include use case diagrams, activity diagrams, sequence diagrams, ERD (Entity Relationship Diagram), and user interface design. The system is designed as a web-based application that allows users to log in, upload and download documents, create folders, and share archives through digital links. Storage is managed on a cloud server to ensure data availability and security. The results show that the developed system successfully addresses the institution's problems, such as accelerating document retrieval, reducing the risk of data loss, and simplifying administrative tasks related to archiving. Additionally, the system supports the reduction of paper usage and aligns with government digitalization initiatives.